(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Educational games have become an increasingly popular tool in teaching English to young learners. This article explores the role of educational games in enhancing language acquisition and proficiency among young learners. It discusses the benefits of using games as a teaching tool, including increased engagement, motivation, and enjoyment in the learning process. The paper also examines the different types of educational games that can be used to teach English, such as board games, online games, and role-playing activities. Additionally, it discusses the importance of incorporating educational games into the curriculum to create a more interactive and immersive learning experience for young learners. Finally, the paper highlights the potential challenges and limitations of using educational games in teaching English to young learners and offers suggestions for overcoming these obstacles. Overall, this paper emphasizes the significant role that educational games play in facilitating language learning and promoting a positive learning environment for young English language learners.